2014
DOI: 10.1002/adfm.201400011
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Nanoparticles Encased in a Cyclodextrin Complex Shell for Potential Site‐ and Sequence‐Specific Drug Release

Abstract: Time-staggered combination chemotherapy strategies show immense potential in cell culture systems, but fail to successfully translate clinically due to different routes of administration and disparate formulation parameters that preclude a specifi c order of drug presentation. A novel platform consisting of drug-containing PLGA polymer nanoparticles, stably fashioned with a shell composed of drug complexed with cationic cyclodextrin, capable of releasing drugs time-and sequence-specifi cally within tumors is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…We here emphasize that the goal of the paper was to formulate a computational framework for modeling complex problems such as convective-diffusive transport in organs or tumors, so that the presented results give basically a qualitative confirmation of the methodology. Quantitative verification of accuracy of models, which are incorporated into the methodology of this study, was partly given in our previous references [27,32,19,34], and the results are in agreement with general observations in experiments. We present two examples which demonstrate applicability of the developed computational model to two very different conditions, one is a tumor with extremely small dimensions and the other is an organ with an order-ofmagnitude larger dimensions and different material parameters.…”
Section: Implementation Of the Computational Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…We here emphasize that the goal of the paper was to formulate a computational framework for modeling complex problems such as convective-diffusive transport in organs or tumors, so that the presented results give basically a qualitative confirmation of the methodology. Quantitative verification of accuracy of models, which are incorporated into the methodology of this study, was partly given in our previous references [27,32,19,34], and the results are in agreement with general observations in experiments. We present two examples which demonstrate applicability of the developed computational model to two very different conditions, one is a tumor with extremely small dimensions and the other is an organ with an order-ofmagnitude larger dimensions and different material parameters.…”
Section: Implementation Of the Computational Modelsupporting
confidence: 78%
“…can dominate the transport through the wall. This interaction on a molecular level may be incorporated into a continuum transport model by evaluation of the effective diffusion coefficients (or scaling functions) using MD procedures and a numerical homogenization (within a multiscale-hierarchical concept); such a multiscale model has been applied to various bioengineering problems [19,[27][28][29][30][31][32][33][34][35]. Briefly, the following steps are undertaken in formulating the multiscale model.…”
Section: Fundamental Equations For Transport Within Capillariesmentioning
confidence: 99%
“…Full details concerning fluorophore release, as in the case of nanoparticle fabrication and characterization can be found presented in [24]. Briefly, fluorophores were released into PBS and the concentration of both determined using a Synergy H4 Hybrid Reader and a previously established calibration curve.…”
Section: Methodsmentioning
confidence: 99%
“…Our recently developed computational multiscale transport theory and methodology enabled us to couple molecular and micro-scales for better prediction of drug transport. 18,27,28 We have used the systemic PK and characteristic pathology information to feed the transport models for the 3LL and 4T1 tumors. The kinetics of DOX accumulation showed that the DOX retention overcomes limitations of poorer diffusing DOX-loaded liposomes (PLD).…”
Section: Transport Models In Drug Deliverymentioning
confidence: 99%